DIGITAL TECHNOLOGIES IN TOURISM AND THEIR IMPORTANCE (Journal of Universal Science Research, 2025)
The development of the tourism sector is inseparably linked with modern technologies. Digital technology plays a major role in automating tourism services, creating convenience for tourists, and optimizing business processes. This article discusses in detail the current state of digital technologies in tourism, their impact, and future development trends. Technologies such as artificial intelligence (AI), virtual reality (VR), blockchain, and the Internet of Things (IoT) are analyzed, along with new trends like the metaverse, biometric security systems, and eco-sustainable tourism. The study also addresses the advantages and disadvantages of these technologies.